The potential of stable carbon isotope ratios and leaf temperature as proxies for drought stress in banana under field conditions - Vantyghem, M.; Merckx, Roel; Stevens, B.; Hood-Nowotny, R.; Swennen, Rony L.; Dercon, G. (Elsevier, 2022)
Drought stress is a major limiting factor for banana production and the incidence of drought spells is expected to increase with climate change. Climate smart practices and varieties are needed, but evaluation in the field is hampered by a lack of reliable physiological drought stress indicators. We investigated the potential of using stable carbon isotope ratios (δ13C) and leaf temperature and its derived DANS (Degrees above Non-Stressed Canopy) index as proxies for drought stress in banana. Leaf samples were taken for δ13C analysis and leaf temperature was monitored throughout the day in a field trial with different banana plant stages (mother and daughter plants) under two irrigation treatments (rainfed and irrigated) during the dry season in Arusha, Tanzania. We found that δ13C, leaf temperature and DANS were highly sensitive proxies for drought stress in banana. Soil volumetric water content had a significant effect on both δ13C values and DANS. There was a significant difference in δ13C (1.5 ± 0.1‰, p < 0.01) and afternoon leaf temperature (7 ± 1 °C, p < 0.01) between the rainfed and irrigated treatment. To deal with variability in δ13C within the leaf, we developed a banana tailored sampling method. This study also revealed the complexity of carbon isotope dynamics in the intertwined system of mother and daughter plants. Daughter plants had more negative δ13C values (−1.9 ± 0.1‰, p < 0.01) and lower temperatures (4 ± 1 °C) than mother plants. This indicates less stress, but interpretation of the δ13C ratio is complicated by the potential carbon flux from mother to daughter plant. Once we have a full understanding of these complexities within the plant, the δ13C and leaf temperature based methods we developed, can be directly implemented for both mother and daughter plants under various field conditions.